An Efficient Control of Virus Propagation - Madihah Mohd Saudi; Shaharudin Ismail (2024)
There are very few studies done in dealing with computer viruses in Malaysia. By realizing that, this research paper is done in managing of virus problem among ICT (Information Communication and Technology) users in Malaysia. Firstly, this research is establishing the existence of the problem through a questionnaire survey. This questionnaire survey was carried out at Malaysia specifically at Klang Valley and Putrajaya. Then a study was made on classifying virus, studying their symptoms and behaviour with the aim of controlling its propagation by studying their known features. The control is intended via a newly developed system which has been built applying Artificial Intelligent (Case-Based Reasoning) and Object Oriented Methodology. The ECOVP (Efficient Control of Virus Propagation) system that was developed is capable of educating users in handling computer virus incidents and at the same time helps to control computer virus propagation.